Упростите выражение: 1) x 3 k y 2 n : x 6 k y 5 n , где k и n − целые числа; 2) a k + 5 ∗ b k + 3 c 3 k + 2 : a k + 3 ∗ b k + 2 c 2 k + 1 , где k − целое число; 3) ( x n + 3 y n ) 2 − 12 x n y n x 3 n + 27 y 3 n : x 2 n − 9 y 2 n ( x n − 3 y n ) 2 + 12 x n y n , где n − целое число.
x 3 k y 2 n : x 6 k y 5 n = x 3 k y 2 n ∗ y 5 n x 6 k = y 5 n − 2 n x 6 k − 3 k = y 3 n x 3 k
a k + 5 ∗ b k + 3 c 3 k + 2 : a k + 3 ∗ b k + 2 c 2 k + 1 = a k + 5 ∗ b k + 3 c 3 k + 2 ∗ c 2 k + 1 a k + 3 ∗ b k + 2 = a k + 5 − ( k + 3 ) ∗ b k + 3 − ( k + 2 ) c 3 k + 2 − ( 2 k + 1 ) = a k + 5 − k − 3 ∗ b k + 3 − k − 2 c 3 k + 2 − 2 k − 1 = a 2 b c k + 1
( x n + 3 y n ) 2 − 12 x n y n x 3 n + 27 y 3 n : x 2 n − 9 y 2 n ( x n − 3 y n ) 2 + 12 x n y n = ( x n + 3 y n ) 2 − 12 x n y n x 3 n + 27 y 3 n ∗ ( x n − 3 y n ) 2 + 12 x n y n x 2 n − 9 y 2 n = x 2 n + 6 x n y n + 9 y 2 n − 12 x n y n ( x n + 3 y n ) ( x 2 n − 3 x n y n + 9 y 2 n ) ∗ x 2 n − 6 x n y n + 9 y 2 n + 12 x n y n ( x n − 3 y n ) ( x n + 3 y n ) = x 2 n − 6 x n y n + 9 y 2 n ( x n + 3 y n ) ( x 2 n − 3 x n y n + 9 y 2 n ) ∗ x 2 n + 6 x n y n + 9 y 2 n ( x n − 3 y n ) ( x n + 3 y n ) = ( x n − 3 y n ) 2 ( x n + 3 y n ) ( x 2 n − 3 x n y n + 9 y 2 n ) ∗ ( x n + 3 y n ) 2 ( x n − 3 y n ) ( x n + 3 y n ) = x n − 3 y n x 2 n − 3 x n y n + 9 y 2 n
Если Вы нашли ошибку, неточность или просто не согласны с ответом, пожалуйста сообщите нам об этом